Quality-by-Design Principles Applied to the Establishment of a Pharmaceutical Quality Control Laboratory in a Resource-Limited Setting: The Lab Water. (21st April 2022) - Suleman, Sultan; Belew, Sileshi; Kebebe, Dereje; Duguma, Markos; Teshome, Henok; Hasen, Gemmechu; Evelien Wynendaele,; Duchateau, Luc; De Spiegeleer, Bart
Abstract : Quality-by-design (QbD) is defined as a systematic approach to design and develop a product/service based on sound science and quality risk management. It is already frequently applied in the pharmaceutical industry mainly in the development of pharmaceutical products and analytical methods but is not well established in the setup of facilities like quality control (QC) laboratory (lab). Therefore, lab QbD (lQbD) concept is introduced considering lab water purification system as an example. The water purification system comprising distillation unit coupled with Nanopure Analytical Ultrapure Water System combined with a 0.2-micron filter was established in Jimma University Laboratory of Drug Quality (JuLaDQ). The consistent capability of the established water purification system was evaluated through routine monitoring of the critical quality parameters (i.e., physicochemical, HPLC-DAD chromatogram total peak area, and resistivity) of freshly prepared lab water for a period of one year. In addition, quality of different grade water (tap water, distilled water (before and/or after cleaning distillation unit), and fresh ultrapure water (18.2 MΩ × cm at 25°C)) used in JuLaDQ was evaluated. The results of routine analysis of water quality revealed that HPLC global peak area at 210 and 254 nm could serve as one of the discriminatory control strategies to evaluate the capability of water purification system to produce the desired quality of lab water; and thus, we proposed a specification limit of 5, 000 mAU∗s and 5, 500 mAU∗s for global peak area at 254 and 210 nm, respectively, as system suitability parameter.